Population dynamics of the yellow piranha Serrasalmus spilopleura Kner, 1858 (Characidae, Serrasalminae) in Amazonian floodplain lakes - doi: 10.4025/actascibiolsci.v35i3.15749 - Fabricio Barros de Sousa; Maria Gercilia Mota Soares; Luiza Prestes (Acta Scientiarum. Biological Sciences, 2013)
Fish is the main source of protein in the Amazon and fishing is one of the most important sources of income for the Amazonian population. Serrasalmus spilopleura is a species that have been increasingly consumed by riverside communities, although it is only occasionally commercialized at regional markets. Therefore, this work sought to generate information about the population biology of S. spilopleura captured in floodplain lakes, Jaitêua and São Lourenço, in Manacapuru, Amazonas State. The population parameters were estimated by analyzing the distribution of the length frequency with the help of the ELEFAN I routine of the FISAT II program. The weight/length relationship was estimated by linear regression, longevity by Taylor’s method, rate of natural mortality by Taylor’s and Pauly’s methods, and growth type by a t-test (α = 0.05). 669 specimens of S. spilopleura were captured measuring between 7 and 22 centimeters. The estimated population parameters were: k = 0.34 year-1, L∞ = 23.10 cm, t0 = 0, and A0.95 = 9 years. 7 cohorts were identified, Taylor M = 0.33 year-1 and Pauly M = 0.98 year-1. The weight/length relationship equation was Wt = 0.051320.Lt2.8727, and negatively allometric growth. The information on the population parameters of S. spilopleura could be used to provide evaluation models for this fishery resource.